Periodical Professional Publications as the Basis of Historical and Pedagogical Researches of Problem of Postgraduate Pedagogical Education Development in Ukraine - Prymakova, Vitaliya (Pedagogical Discourse, 2013)
The article is devoted to the analysis of influence of periodical professional publications study on the objectivity and authenticity of historical and pedagogical researches, particularly the problem of the development of postgraduate education of primary school teachers in Ukraine (period from the second half of the ХХ-th century till nowadays). The contemporary state of the given problem, content and character of pedagogical periodicals publications in the defined period has been analysed; the role of primary schools teachers in the professional development has been determined; principles and criteria of such analysis have been specified; groups of sources in native professional periodical press of Soviet and post Soviet periods in education development in Ukrainian society have been characterized.